Climate justice and energy: applying international principles to UK residential energy policy. Issue 4 (3rd April 2017) - Mayne, Ruth; Fawcett, Tina; Hyams, Keith
ABSTRACT: This paper draws on climate justice principles developed in the context of international negotiations between national governments to assess the distribution of carbon reduction roles between different actors involved in residential energy use within the UK. In so doing, it aims to provide a new understanding of equity aspects of current residential policy and to highlight opportunities for more effective and equitable policy. The paper uses three criteria: rights and corresponding duties; mitigation responsibilities and capabilities. It applies them systematically to assess the roles of five key actors involved in residential energy use in the UK. The assessment finds a suboptimal distribution of actors' duties, responsibilities and capabilities and roles and discusses whether and how a more effective and fair allocation of outcomes, in terms of carbon reduction and fuel poverty, could be achieved. In particular, it raises questions about whether the right actors are being legally obliged or incentivised to deliver energy efficiency improvements, and suggests that particular actors – local authorities and community groups – are under-used and require greater government support with capability. The paper represents the first use of international climate justice frameworks to investigate residential energy policy within a country.